2017
DOI: 10.1111/jphs.12183
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of community pharmacists’ perceptions of healthcare services in Saudi Arabia

Abstract: Objectives The pharmacist faces need to provide clinical services to the patients and then the actual proficiency of the pharmacist can be judged. The aim of the study was to evaluate the elements of clinical knowledge, needs for clinical services, value of practice and confidence to practice among expatriate pharmacists (EPs) working in community pharmacies. Also determine the correlation pattern between the rudiments. Methods A survey‐based investigation conducted between December 2015 and May 2016 among EPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 14 publications
(33 reference statements)
2
21
0
Order By: Relevance
“…The majority of community pharmacists in their current practice did not report adverse drug reactions to the MOH of Saudi Arabia . Studies in this systematic review showed that majority of the surveyed community pharmacists dispensed and prescribed antibiotics, antipsychotics, antihypertensive, anti‐diabetics and other non‐over–the‐counter medications upon patient's request only and without a prescription from a physician . A study by Abdulhak et al .…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…The majority of community pharmacists in their current practice did not report adverse drug reactions to the MOH of Saudi Arabia . Studies in this systematic review showed that majority of the surveyed community pharmacists dispensed and prescribed antibiotics, antipsychotics, antihypertensive, anti‐diabetics and other non‐over–the‐counter medications upon patient's request only and without a prescription from a physician . A study by Abdulhak et al .…”
Section: Resultsmentioning
confidence: 84%
“…The present study found that community pharmacists in Saudi Arabia are frequently approached by patients and the general public to seek health‐related advice, medication counselling and for multiple drugs or disease related problems . However, the knowledge and attitude of the majority of community pharmacists in Saudi Arabia are inadequate and unsatisfactory to provide quality patient‐centred care services .…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations